Root length and alveolar bone level of impacted canines and adjacent teeth after orthodontic traction: a long-term evaluation - SILVA, Aldir Cordeiro da; CAPISTRANO, Anderson; ALMEIDA-PEDRIN, Renata Rodrigues de; CARDOSO, Maurício de Almeida; CONTI, Ana Cláudia de Castro Ferreira; CAPELOZZA FILHO, Leopoldino (Journal of Applied Oral Science, 2017)
Objective The aim of this retrospective study was to evaluate the long-term effects of orthodontic traction on root length and alveolar bone level in impacted canines and adjacent teeth. Material and Methods Sample consisted of 16 patients (nine males and seven females), mean initial age 11 years and 8 months presenting with unilaterally maxillary impacted canines, palatally displaced, treated with the same surgical and orthodontic approach. Teeth from the impacted-canine side were assigned as Group I (GI), and contralateral teeth as control, Group II (GII). The mean age of patients at the end of orthodontic treatment was 14 years and 2 months and the mean post-treatment time was 5 years and 11 months. Both contralateral erupted maxillary canines and adjacent teeth served as control. Root length and alveolar bone level (buccal and palatal) were evaluated on cone-beam computed tomography (CBCT) images. The comparison of root length and alveolar bone level changes between groups were assessed by applying paired t-test, at a significance level of 5% (p